Optimization of machining parameters of composites using multi-attribute decision-making techniques: A review. (January 2018) - Arun Ramnath, R; Thyla, PR; Mahendra Kumar, N; Aravind, S
An in-depth literature survey of machining study on fiber-matrix composites is presented in this review paper. The review work mainly focuses on optimization of machining parameters in composite materials with different machining factors. Conventional machining processes such as turning, drilling and milling as well as composite materials which are reinforced with fibers are considered in this study. Machining aspects on various fiber matrix composites has been carried out over a long period of time. In this review work, conflicting conditions of multi-attribute decision-making techniques and machining conditions are focused. The optimization study on machining parameters is done, considering both priori and posteriori approach including advanced optimization techniques. Optimization of machining parameters in fiber reinforced particulate composites has not been explored earlier. The review work on machining study of composites was not attempted earlier and hence this work provides valuable information for subsequent researchers to enhance the scope of research work in particle-reinforced polymer composites.